Español - Rojas Pérez, Lino Arturo (2022)
Introduction. Several factors have influenced the epidemiological evolution of the pandemic, it is essential to understand what effect vaccination has produced in the midst of the SARS-CoV-2 pandemic. Objective. Analyze the epidemiological effect that vaccination against COVID-19 has had on Ecuador. Methodology. A search for information has been carried out in organizations internal and external to Ecuador to contrast the evidence found, in addition, search engines and virtual libraries of scientific articles have been used to acquire a better knowledge about the COVID-19 vaccine and its impact, where it has been chosen the highest quality information. Data analysis has been carried out using observational methods to express measures of frequency and association. Outcome. A strong correlation has been found between community immunity and the cumulative effect of vaccination with the decrease in the number of infections and the number of deaths due to COVID-19. The epidemiological behavior of the pandemic and the effect of vaccination on it have been analyzed from March 1, 2020, to September 19, 2021. Discussion. Vaccination has been a modifier of the epidemiological effect of COVID-19 and the quality of public policies have a direct effect on the health of the population by achieving community immunity. Conclusions. The creation of appropriate public policies has been one of the causes of an accelerated generation of community immunity in Ecuador, especially regarding the "9/100 Vaccination Plan" which can be exported to other countries for its proven effectiveness.